Between declaration and action – an analysis of the results of research on circular behaviours taken up by the households and perceived benefits from them - Szczygieł, Elżbieta; Lwowska, Aleksandra; Hajduk-Stelmachowicz, Marzena (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2022)
The main aim of the paper is to analyse and evaluate the possible relation between taking up of the circular behaviours by the households’ members and perceiving the benefits. The paper presents the results of the research conducted among Polish households on the territory of two voivodeships: Podkarpackie and Małopolskie. In the article the authors present the result of the statistical analysis of the frequency of undertaking those behaviours in the households and perception of the benefits. To indicate the possible dependences the Chi2 Test of Independence and The U Mann-Whitney Test were used. Obtained results indicate that undertaking circular behaviours may have an influence on the perceived benefits of varying magnitude. It could be important due to the establishment of support activities aiming at increasing the overall level of circularity among the households (as an economic sector). The originality of the research consists the methodology used and novel questionnaire prepared by one of the authors. The questionnaire joins 9R’s circularity concept (normally used in circularity assessments in business companies) with typically households’ behaviours. This article is the sixth one in the publication series devoted to circular economy and sustainable development matters.